2009
DOI: 10.1074/jbc.m807610200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor Blockade Increases Bone Mass

Abstract: Renin angiotensin system (RAS) regulates circulating blood volume and blood pressure systemically, whereas RAS also plays a role in the local milieu. Previous in vitro studies suggested that RAS may be involved in the regulation of bone cells. However, it was not known whether molecules involved in RAS are present in bone in vivo. In this study, we examined the presence of RAS components in adult bone and the effects of angiotensin II type 2 (AT2) receptor blocker on bone mass. Immunohistochemistry revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 33 publications
12
70
0
2
Order By: Relevance
“…19) Efforts need to be made to screen those at risk of osteoporosis and identify the potential pathological mechanisms for age-related osteoporosis. Our study is the first to report the gene expression of RAS components in bone tissue by the polymerase chain reaction, in accordance with the results which showed the protein expression of ACE, rennin and angiotensin II receptors in the tibia 6) and femur 20) of mice. The objective of the present study was to elucidate the potential pathological role of local RAS during the process of age-related bone deterioration.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…19) Efforts need to be made to screen those at risk of osteoporosis and identify the potential pathological mechanisms for age-related osteoporosis. Our study is the first to report the gene expression of RAS components in bone tissue by the polymerase chain reaction, in accordance with the results which showed the protein expression of ACE, rennin and angiotensin II receptors in the tibia 6) and femur 20) of mice. The objective of the present study was to elucidate the potential pathological role of local RAS during the process of age-related bone deterioration.…”
Section: Discussionsupporting
confidence: 68%
“…5) Recent studies have shown that such components of RAS as renin, ACE, and Ang II receptors are expressed in the skeleton. 6) Functional studies have revealed that Ang II could stimulate the differentiation and activity of osteoclasts in vivo 7) and in vitro, 8) and that the activation of RAS induced high-turnover osteoporosis with accelerated bone resorption.…”
Section: Involvement Of the Skeletal Renin-angiotensin System In Age-mentioning
confidence: 99%
See 1 more Smart Citation
“…RAS is recognized as contributing to the development of osteoporosis independently of hypertension [17][19], and a blockage of this system either at the level of angiotensin enzyme inhibitor (ACEI) or at the level of angiotensin receptors proved to be beneficial for bone [20], [21]. Beside its anti-hypertensive activity, TEL has a unique ability to bind and activate PPARγ [22], [23] and has a beneficial effects on insulin sensitivity in humans [24][26] and rodents [27].…”
Section: Introductionmentioning
confidence: 99%
“…The whole tissue and cell lysate preparation and immunoblot were performed as previously described (Izu et al, 2009) using rabbit anti-type XII collagen (1:1,000 dilution; KR33), rabbit anti-Cx43 (1:10,000 dilution; Sigma-Aldrich), rabbit anti-mouse collagen I (1:1,000 dilution; Millipore), rabbit anti-Cad11 (1:250 dilution; Invitrogen), rabbit anti-N-cadherin (1:1,000 dilution; Cell Signaling Technology), 0.1 µg/ml of goat anti-mouse osteopontin (R&D Systems), goat anti-osteocalcin (1:100 dilution; Santa Cruz Biotechnology, Inc.), mouse anti--actin (1:5,000 dilution; Millipore), and anti-mouse or anti-rabbit HRP-conjugated secondary antibodies (GE Healthcare).…”
Section: Immunoblotting Analysismentioning
confidence: 99%